Using policy discourses to open up the conceptual space of farm education: inspiration from a Belgian farm education network. Issue 9 (2nd September 2018) - Crivits, Maarten; de Krom, Michiel P. M. M.; Block, Thomas; Dessein, Joost
Abstract: Farm education organized by farmers and directed towards students and groups of citizens is a relatively new practice often considered as one specific business strategy to diversify farmers' income. Although we endorse the importance of an economic rationale we argue that this conceptualization undermines a diversity of perspectives on educative processes that address societal transformation and the political role of intergroup and interpersonal deliberation. In this paper, we start from the observation that on the European level three different competing policy paradigms or discourses are being advocated. Reasoning from a discourse-analytical perspective these policy discourses cannot be considered as mere ideas floating in abstraction but constitute interpretative frames that have concrete implications for practices in the agro-food domain. Along these lines, we reveal three analytically distinct educative practices by specifying how each discourse articulates meaning to make sense of farm education in terms of goals, relations and actions. Our theoretical assumptions on education are informed by John Dewey's pragmatist conception of education which starts from the idea that the mutual recognition of social interests are co-constitutive for the experience of learning. We use a case study on a regional farm education network in Belgium to illustrate how farmer's educative efforts can be enrolled differently in educational practices according to different discursive frames and how these different educational practices enable or constrain social and educational arrangements that promote a sustainability transition. We conclude that farm education is a multifaceted educational practice and reflect on its potentialities and pitfalls to foster (emancipatory) agency to re-balance conflicting interests towards sustainable development.